ROLE OF DIET AND PHYSICAL ACTIVITY ON MENSTRUAL HEALTH - Selvlakshmi S,; Lakshmanan S, (The Bioscan, 2024)
Aim: The objective of the study was to determine the menstrual irregularities among adolescents, and their relationship to dietary and physical activity patterns. Material and method: The cross-sectional survey was carried out in various college students. The questionnaires were designed based on socio-economic characteristics, diet and physical activity, and menstrual abnormalities. Result: Prevalence of dysmenorrhea, and PMS were among adolescent Eating junk food and lack of physical activity was linked to dysmenorrhea (38.5 %) and PMS(45.4%) Conclusion: Health education programs should focus on lifestyle changes such as physical activity, reducing junk food intake and encouraging healthy eating habits to promote menstrual health.